Jesuit Intellectual and Physical Exchange between England and Mainland Europe, c. 1580-1789
1 online resource.
Keywords: Jesuit Intellectual and Physical Exchange between England and Mainland Europe, c. 1580-1789: ‘The World is our House’? offers new perspectives on the English Mission of the Society of Jesus. It brings together an interdisciplinary and international group of scholars to explore the Mission’s role and wider impact within the Society, as well as early modern European Catholicism. Building on recent movements within the field to decentralise the Catholic Reformation, the volume seeks to change perceptions of the English Mission as peripheral, bringing the archipelagic experience of Jesuits working in the British Isles in line with work on their European confreres and the broader global network of the Society of Jesus.